Specific binding of neoglycoproteins to Toxoplasma gondii tachyzoites. - Robert, R (1991)
Several studies have shown that protozoa bind to glycoproteins or neoglycoproteins. Here we report that Toxoplasma gondii binds strongly to bovine serum albumin-glucosamide. The binding was rapid, time dependent, partially reversible, saturable, and specific. Scatchard analysis showed about 40,000 molecules of bovine serum albumin-glucosamide per toxoplasma cell. The apparent dissociation constant was found to be 4.46 x 10(-8) M.